2020
DOI: 10.1021/acs.langmuir.0c00959
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Segregation of Microspheres by Rubbing-Induced Triboelectrification on Patterned Surfaces

Abstract: Particle (monolayer) assembly is essential to various scientific and industrial applications, such as the fabrication of photonic crystals, optical sensors, and surface coatings. Several methods, including rubbing, have been developed for this purpose. Here, we report on the serendipitous observation that microparticles preferentially partition onto the fluorocarbon-coated parts of patterned silicon and borosilicate glass wafers when rubbed with polydimethylsiloxane slabs. To explore the extent of this effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 50 publications
4
42
0
Order By: Relevance
“…Summarizing, consistent with our previous studies, 36,72 the data displayed in both Fig. 12 and 13 jointly show that, as a result of the tribocharging mechanism, the silica or polystyrene particles, independent of their size, and the CF x -coated substrates acquire opposite charges, positive and negative, respectively, after agitating the system.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Summarizing, consistent with our previous studies, 36,72 the data displayed in both Fig. 12 and 13 jointly show that, as a result of the tribocharging mechanism, the silica or polystyrene particles, independent of their size, and the CF x -coated substrates acquire opposite charges, positive and negative, respectively, after agitating the system.…”
Section: Resultssupporting
confidence: 91%
“…However, as reported in previous studies, 36,72 no significant change in surface potential was measured on the surface of the particles or substrate in the case of the bare silicon substrates (not shown). A moderating remark in this respect is that, also in this case, it proved to be challenging to measure the charge on the particles after agitating them on the bare silicon substrate.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Following the rationale to reduce particle adhesion, the silica particles would preferentially stick onto the silicon surfaces, whereas in the present study consistently the opposite is observed. We believe the clue to this observation can be found in our recent study, [97] where we have shown that rubbing-induced tribocharging leads to a preferential adherence of silica particles to CF x -coated surfaces (cf. Chapter 6).…”
Section: Experiments Performed Using Silica Particles With Uncoated S...mentioning
confidence: 81%
“…Electrode in a Strong Electric Field of the CF x -coated wafers is described in our recent work [97] . The native oxide layer, typically of ca.…”
Section: A Detailed Study Of the Interaction Between Levitated Micros...mentioning
confidence: 99%